Effect of biopolymer coatings made of zein nanoparticles and ε-polylysine as postharvest treatments on the shelf-life of avocados (Persea americana Mill. Cv. Hass) - Garcia, Franciela; Lin, Wei-Jen; Mellano, Valerie; Davidov-Pardo, Gabriel (Journal of agriculture and food research, 2022)
Avocados (Persea americana) are a popular fruit produced and consumed all around the world. Due to their climacteric nature, they are predisposed to rapid loss of moisture and firmness after harvest and prior to sale. The prevalence of the fungal phytopathogen Colletotrichum spp. Exacerbates the rate of decay by causing anthracnose, resulting in relatively short shelf-lives, increased waste, and economic losses. The objective of this study was to assess the effect of coatings made of zein nanoparticles (ZNP), zein and ε-polylysine nanoparticles (ZPL), zein solution (ZS), and ε-polylysine solution (PL) on the weight loss, respiration rate, firmness, color, and fungal decay of avocados compared to a control (C). By day 15 in ambient storage, control avocados had scarred surfaces, significant color change, overripe pulp, and clear signs of fungal decay. At this time, avocados treated with ZPL lost the least weight, 20.14%, compared to the control, 28.05%. The lowest respiration rates were seen in ZPL treatment with values of 107.83 mg of CO2/kg/h. The flesh of the ZPL- and ZNP- treated fruit remained firmer, 5.01 and 4.07 N, respectively, compared to the control, 3.67 N. For pulp color, ZPL-treated fruit showed the smallest color difference as measured by total color change, ΔE, 3.67 compared to the control, 15.45. At the conclusion of a 15-day Colletotrichum spp. inoculation study, ZPL treated avocados had the significantly lowest fungal severity score of 3.33, while ZNP-treated fruit and the control had scores of 4 and 4.7, respectively. The results of this project support biopolymeric coatings as a novel technique with the potential to extend shelf-life and reduce avocado waste both at retail and household levels to possibly mitigate economic losses. [Display omitted] •Storage stability of avocados coated with zein (Z) and/or polylysine (PL) was tested.•Avocados coated with nanoparticles made of Z showed the least changes during storage.•PL in the nanoparticles reduced the severity of anthracnose in inoculated avocados.•Coatings made with the ZPL nanoparticles extended avocado shelf-life.